206 Use of non-invasive vagal nerve stimulation in a tertiary headache service. Issue 6 (27th May 2022) - Lowe, Michael; Gorrie, George; Dani, Krishna; Selvarajah, Johann; Tyagi, Alok
Abstract : Introduction: Non-invasive vagal nerve stimulation (nVNS) is a novel treatment modality for primary headache disorders. There is some clinical trial evidence to support its use, both as an abortive and pre- ventative treatment, in cluster headache and migraine. We evaluated the use of this novel treatment in a regional tertiary headache service. Methods: A retrospective analysis of case notes of all patients currently using nVNS in our service was undertaken. Other current and previous headache treatments were recorded. A subjective assessment of response to nVNS was made based on available clinical data. Results: 21 patients currently using nVNS were identified. Diagnoses were chronic cluster headache (n=12), episodic cluster headache (n=1), migraine (n=4), hemicrania continua (n=3) and SUNCT (n=1). All current users reported some degree of positive response to nVNS, with 14 (67%) assessed as having a large improvement. The most frequently reported improvement parameter was reduction in headache frequency (15, 71%). Those reporting a large improvement used significantly fewer concurrent preventa- tive medications (median 0 vs. 2.5, p=0.033). Conclusions: In this small group of patients with a variety of headache diagnoses nVNS has been an effective treatment; this appears to be due to efficacy as a preventative treatment. michaelcmlowe@gmail.com